Understanding and neutralising covid-19 misinformation and disinformation - Wang, Yuxi; Bye, John; Bales, Karam; Gurdasani, Deepti; Mehta, Adityavarman; Abba-Aji, Mohammed; Stuckler, David; McKee, Martin (BMJ (Online), 2022)
Yuxi Wang and colleagues say that the public inquiry on covid-19 must look at who was opposing public health measures and why and should call on public health authorities to engage more effectively with the threats of infodemics